ACCOUNTING AND THE S.E.C. (The Accounting Review, 1938)
Abstract The article focuses on accounting and the Securities and Exchange Commission. Five new cases have been supplied by the Securities and Exchange Commission illustrating various points in registration and annual statements submitted to the Commission by business corporations. In each case an issue of accounting procedure is raised in which the administrative staff of the Commission has recommended changes. While these cases do not necessarily establish precedents, their effect on accounting practice is unquestioned. Names of the corporations involved will be supplied to any reader who desires further study of the cases. The financial statements of a utility company when originally filed included an auditor's certificate which explained that the company followed the retirement-reserve method of providing for electric and water-department properties retired from service, and that the provisions for retirements deducted from earnings were substantially less than the amounts deducted for depreciation in Federal income tax returns, which amounts were computed on the basis of age and estimated life of depreciable properties.